Teachers’ learning driven by “multi-subject needs”: Implication, mode and strategies - Yuebo Yu; Jiapan Xu; Zalik Nuryana (International Journal of Education and Learning, 2023)
Under the influence of the concept of lifelong learning, teachers’ learning has become the main paradigm of teacher development. The traditional training for primary and secondary school teachers often pays too much attention to the transmission of theories and ignores the practical needs of teachers, resulting in the dilemma of low learning efficiency and poor effect. In order to break through the current learning dilemma of primary and secondary school teachers and meet the needs of students’ growth and long-term development of schools, on the basis of clarifying the basic implication of teacher learning driven by “multi-subject needs”, this paper introduces the Activity Theory to discuss the implications of teacher learning, constructs the teacher learning mode driven by “multi-subject needs,” and analyzes the operating mechanism of this learning mode. In order to promote the effective operation of this mode, teachers should set up the concept of lifelong learning, adhere to the self-orientation of learning, and pay attention to learning reflection. The school level should create a cultural atmosphere for teachers’ learning, make clear the purpose of teachers’ learning, let teachers’ pay attention to the practical situation, and make teachers’ learning become a normal activity.